Electroflotocoagulation wastewater treatment of LLC «Kolomyia meat-processing plant» - Угляр, Юлія Михайлівна; Борщишин, Ірина Дмитрівна; Хром’як, Уляна Володимирівна (Eastern-European Journal of Enterprise Technologies, 2014)
The experimental studies of using bentonite clay of the Sokyrnytsia field in Khust district (Transcarpathian region) for wastewater treatment (WW) were conducted. They actively absorb such pollutants as sulfates, chlorides, heavy metals and others. Also, the use of bentonite in wastewater treatment makes it possible to reduce the load on the microorganisms in aerotanks, reduce the content of ammonia nitrogen, suspended substances and BOD5 (biochemical oxygen demand) in WW. The possibility of wastewater treatment of "Kolomyia meat-processing plant" using natural montmorillonite, modified with iron hydroxide during electroflotocoagulation treatment. The optimum conditions of wastewater treatment process (sorbent dose, current density, duration of WW treatment) were determined. According to the results, the optimal parameters of the treatment process include: sorbent dose is 30 mg/dm3, current density is 60 А/m2, treatment time is 3 min. Based on the analysis of the existing methods of industrial wastewater treatment and the obtained experimental data the most effective method was proposed and the feasibility of replacing the existing flow diagram of "Kolomyia meat-processing plant" wastewater treatment was justified.